Risk factors for intracerebral hemorrhage in patients undergoing maintenance hemodialysis - Yu-Huan, Song; Guang-Yan, Cai; Yue-Fei, Xiao (Frontiers in Neurology, 2023)
Abstract Background: In haemodialysis patients, intracerebral haemorrhage (ICH) is the main cause of mortality among stroke subtypes. It is unclear whether, along with traditional cardiovascular risk factors, risk factors unique to the uraemic environment, such as the abnormal metabolism of intact parathyroid hormone (iPTH), can contribute to the risk of ICH in these patients. Methods: This retrospective case‒control study included twenty-two haemodialysis patients with ICH at a single centre between June 30, 2015 and October 10, 2021. The controls were 95 maintenance haemodialysis patients treated at the same dialysis centre in July 2020. We compared the characteristics of ICH patients with those of the control group to identify factors that contributed to the development of ICH. Results: ICH was located in the basal ganglia (11/22), cerebellum (6/22), and brainstem (6/22) in the 22 patients. Sixteen patients died in the first 16 days due to neurological complications. Univariate analysis showed significant differences in systolic BP, diastolic BP, iPTH and high-density lipoprotein between the two groups (p<0.05). Multivariate logistic regression analysis showed that higher systolic BP (OR, 1.052; 95% CI, 1.016-1.089; p =0.004) and higher iPTH (OR, 1.005; 95% CI, 1.001-1.009; p =0.008) were associated with the onset of ICH. ICH was predicted by systolic BP and iPTH by receiver operating characteristic (ROC) curve analysis, with areas under the curve (AUCs) of 0.732 and 0.624, respectively. The optimal cut-offs for systolic BP and iPTH were 151.9 mmHg and 295.4 pg/ml, respectively. Restricted cubic spline showed that the shape of the association of iPTH with the risk of ICH was approximately J-shaped (P for non-linearity <0.05). Conclusions: Higher systolic BP and abnormal iPTH metabolism might be associated with ICH in haemodialysis patients. Comprehensive control of hypertension and iPTH may still be a fundamental preventive strategy for ICH in these patients.